PENGARUH TEKNOLOGI OFF-SEASON TERHADAP PRODUKSI DAN PENDAPATAN PETANI MANGGA GEDONG GINCU - Sukmawati, Dety; Marina, Ida; Mahmiludin, Dede (Journal of Innovation and Research in Agriculture, 2025)
The production of Gedong Gincu mango is highly dependent on seasonal harvest patterns, leading to fluctuations in production and farmers’ income. Off-season technology has been developed as an innovative cultivation approach to regulate flowering and fruiting periods, enabling mango production outside the natural harvest season. This study aims to analyze the effect of off-season technology on the production and income of Gedong Gincu mango farmers. The research was conducted in Mekarjaya Village, Kertajati Subdistrict, Majalengka Regency, one of the main production centers for Gedong Gincu mango. A quantitative research approach was employed using descriptive analysis, simple linear regression, and path analysis. Data were collected through a survey of 30 mango farmers who had implemented off-season technology. The results indicate that off-season technology has a significant effect on mango production but does not have a direct effect on farmers’ income. Production has a significant effect on farming income, indicating that production plays a key role in determining the success of off-season technology in increasing farmers’ income. These findings suggest that income improvement through off-season technology depends largely on the effectiveness and efficiency of production enhancement. Therefore, optimizing the application of off-season technology should focus on strengthening production to sustainably increase the income of Gedong Gincu mango farmers.